Green School Management in State High School - Nurkhasanah, Nurkhasanah; Wuryandini, Endang; Sudana, I Made (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study analyzes the management of the green school program at Bandar 1 State Senior High School, Batang Regency, with a focus on planning, implementation, and supervision. A qualitative phenomenological method was used to explore the experiences of the school community. The research was conducted directly by the researcher through observation, face-to-face interviews with informants, and documentation of green school activities and administration. The data obtained were collected for data filtering to become concise and focused data, data presentation in the form of narrative text, and ended with conclusions and verification (Miles and Huberman, 2019). The results of the study show 1) Planning is carried out at the beginning of the school year by involving the school community including the preparation and/or adjustment of the school's vision and mission, preparing the Education Unit Curriculum (KSP) and the School Budget Activity Plan (RKAS); 2) The implementation of green schools includes a) school policies that support environmental care such as socializing the school's vision and mission through social media, managing organic and inorganic waste, managing water and electricity wisely, and innovating environmentally friendly behavior; b) Implementation of environmentally friendly curriculum through planning and implementation of environmental-based learning, habituation of clean and healthy living, extracurricular activities that care about the environment in the form of ENVIRO and honey bees; c) Implementation of environmentally friendly supporting facilities is realized in the form of providing cleanliness facilities and environmental management such as the provision of clean water, separate trash bins, sanitation management, school forests and gardens, green open spaces and gazebos for learning; d) Implementation of participatory-based activities in the form of involvement of all school residents in cleanliness programs, management of school gardens, involvement in various environmental actions and support from parties outside the school such as the Environmental Agency (DLH) and the Agriculture Agency; 3) Supervision is carried out routinely after the end of activities, monthly, quarterly, end of semester and end of school year by comparing achievements with the initial targets of the green school program.